Current perspectives of using vitamin D in clinical practice - S.V. Mal'tsev (LCC «Medicine-Inform», 2022)
S.V. Maltsev Russian Medical Academy of Continuous Professional Education, Moscow, Russian Federation An approach to problem solving in public health has revived interest to the prevalence rate of vitamin D deficiency, its role in the pathogenesis of various disease, and strategies for treating vitamin D deficiency. The article presents updates on vitamin D metabolism - its classical and non-calcemic actions. The emphasis is made on the effects of its individual metabolites and other components of the vitamin D endocrine system, such as hydrolase, vitamin-D receptors, and vitamin-D-binding protein (VDBP). The functions of vitamin D are characterized as genomic and non-genomic, including immunomodulatory effect. In particular, the role of vitamin D in patients with COVID-19 is elucidated. The vitamin-D endocrine system plays a special role during pregnancy and in children of all age groups. The article highlights the latest data on vitamin D provision, individual variability in the responses to the same vitamin D dose, as well as the findings of a new research area relating to the content of vitamin D metabolites in food of animal origin. Also, it describes vitamin D intoxication which is usually linked to the impaired regulation of vitamin D metabolism. The clinical efficacy of cholecalciferol agents is demonstrated. Keywords: cholecalciferol, vitamin D metabolism, vitamin D-endocrine system, pregnant women, children, adolescents, vitamin D provision, individual response to vitamin D, food of animal origin, vitamin D intoxication, hypervitaminosis D. For citation: Maltsev S.V. Current perspectives of using vitamin D in clinical practice. Russian Journal of Woman and Child Health. 2022;5(3):244-252 (in Russ.). DOI: 10.32364/2618-8430-2022-5-3-244-252.